2015
DOI: 10.1123/kr.2013-0012
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Fundamental Motor Skill Competence and Physical Activity During Childhood and Adolescence: A Systematic Review

Abstract: The purpose of this review is to synthesize the evidence of the relationship between fundamental motor skills (FMS) competence and physical activity by qualitatively describing results from 13 studies that met rigorous inclusion criteria. Inclusion criteria: (a) published in a peer-review journal, (b) participants were between the ages of 3–18, (c) participants were typically developing, (d) FMS was measured by a process-oriented assessment, (e) assessed physical activity, (f) related FMS and physical activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
224
3
18

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 306 publications
(257 citation statements)
references
References 0 publications
12
224
3
18
Order By: Relevance
“…O fato de crianças estarem envolvidas com esporte durante a infância pode ser um fator que contribua para a aquisição e o refinamento de habilidades motoras básicas 15,[17][18][19][20][21]23 . Isto é, à medida que a criança explora as oportunidades que o ambiente proporciona, as habilidades motoras são refinadas de modo que há aumento de competência e, consequentemente, maior capacidade de se adaptar às exigências do contexto 16,[30][31][32] . Neste caso, oportunidades de prática esportiva orientada, ou seja, prática sistematizada fora do contexto de aulas de educação física podem ampliar a quantidade de estímulos ambientais, de forma a contribuir com o processo de aquisição e diversificação de habilidades básicas 15,33 .…”
Section: Discussionunclassified
“…O fato de crianças estarem envolvidas com esporte durante a infância pode ser um fator que contribua para a aquisição e o refinamento de habilidades motoras básicas 15,[17][18][19][20][21]23 . Isto é, à medida que a criança explora as oportunidades que o ambiente proporciona, as habilidades motoras são refinadas de modo que há aumento de competência e, consequentemente, maior capacidade de se adaptar às exigências do contexto 16,[30][31][32] . Neste caso, oportunidades de prática esportiva orientada, ou seja, prática sistematizada fora do contexto de aulas de educação física podem ampliar a quantidade de estímulos ambientais, de forma a contribuir com o processo de aquisição e diversificação de habilidades básicas 15,33 .…”
Section: Discussionunclassified
“…is not effective, the impact of the intervention itself will be limited. This trend is also demonstrated overall in FMS interventions for general populations (Logan et al, 2011(Logan et al, , 2015Morgan et al, 2013). Even when demonstrating overall positive potential, without including how the intervention was done, it is unlikely that the study outcomes could be replicated.…”
Section: Current Research On Motor Interventions For Asdmentioning
confidence: 92%
“…Recent research has started to demonstrate the importance of building motor skills (Cattuzzo et al, 2016;Logan et al, 2015) and the role motor development plays in other developmental processes for children with ASD (Bedford et al, 2016;Landa & Kalb, 2012). Further, recent research has demonstrated that the development of motor skills for children with ASD is delayed in comparison to peers, starting at an early age (Lloyd et al, 2013) and continuing into adolescence (Staples & Reid, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations